WOKÓŁ INTUICYJNYCH DECYZJI SĘDZIEGO - Zyzik, Radosław (Zeszyty Prawnicze, 2016)
ON A JUDGE’S INTUITIVE DECISIONS Summary The paper discusses the credibility of legal decisions taken on the basis of intuition. An analysis is conducted from the perspective of cognitive psychology, with special emphasis on research on expertise intuition. The aim is to answer the question whether we can speak of trustworthy intuitive decision-making in the legal sciences. I confront research on legal theory conducted by American legal realists with cognitive psychology in order to establish the conditions influencing the decision-making process and the formulation of intuitive evaluations. The paper ends with a presentation of a decision-making model valid both for the legal sciences and for cognitive psychology.